TcA, the putative transposase of the C. elegans Tc1 transposon, has an N-terminal DNA binding domain. - Schukkink, R F (1990)
Tc1 is a transposon present in several copies in the genome of all natural isolates of the nematode C.elegans; it is actively transposing in many strains. In those strains Tc1 insertion is the main cause of spontaneous mutations. The transposon contains one large ORF that we call TcA; we assume that the TcA protein is the transposase of Tc1. We expressed TcA in E.coli, purified the protein and showed that it has a strong affinity for DNA (both single stranded and double stranded). A fusion protein of beta-galactosidase and TcA also exhibits DNA binding; deletion derivatives of this fusion protein were tested for DNA binding. A deletion of 39 amino acids at the N-terminal region of TcA abolishes the DNA binding, whereas a deletion of 108 C-terminal amino acids does not affect DNA binding. This shows that the DNA binding domain of TcA is near the N-terminal region. The DNA binding capacity of TcA supports the assumption that TcA is a transposase of Tc1.